Structural and Functional Characterization of L-Enduracididine Biosynthetic Enzymes - (:unkn) unknown (My University, 2020)
The mannopeptimycins produced by Streptomyces hygroscopicus are non-ribosomal peptide antibiotics with activity against a number of Gram-positive pathogens, including drug-resistant strains like methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE). Attempts to synthesize more potent mannopeptimycin analogues have so far not been successful. One reason this has proven difficult is that the mannopeptimycins contain the unusual non-proteinogenic amino acid L-enduracididine (L-End), or its hydroxylated derivative β-hydroxy enduracididine (βhEnd,). This amino acid is not commercially available and, while synthetic routes have been developed, they are multi-step processes starting from an advanced intermediate. Understanding enzymatic synthesis of L-End is an important goal, because it may lead to a more efficient enzymatic or chemoenzymatic route to this interesting building block.The first enzyme in the L-End pathway is MppP, an unprecedented PLP-dependent L-Arg oxidase that catalyzes a 4-electron oxidation to give 4-hydroxy-2-ketoarginine (4HKA). Our previously proposed mechanism involved several speculative steps lacking the support of experimental data characterizing the species involved, such as the formation of 4,5-unsaturated intermediate and superoxide anion. Through the use of pre-steady state kinetics studies, EPR spectroscopy, and NMR spectroscopy, this work has provided answers to several outstanding questions regarding the mechanism of MppP. In addition to MppP, the L-End pathway contains another unusual enzyme whose apparent function is completely different from that predicted by sequence analysis. MppR was predicted to be an acetoacetate decarboxylase (ADC), but structural studies suggested that MppR was likely responsible for the conversion of 4HKA to 2-ketoenduracididine (2KE). However, this activity had not been demonstrated kinetically owing to the lack of an assay. This study has confirmed and quantified turnover of 4HKA to 2KE by MppR through a development of a quenched-flow LC-MS/MS assay. Preliminary kinetic studies and substrate screening of MppQ have also been carried out, confirming its role as a bona fide aminotransferase responsible for catalyzing the final step in the synthesis of L-End. Through characterization of all enzymes involved, this work represents a significant advance towards the complete understanding of L-End biosynthesis.
Keywords: Antibiotics; Enduracididine; Mannopeptimycin; MppP; Oxidase; Pyridoxal-5’-Phosphate